Efficiency in the Delivery of Social Protection Benefits and Services to Beneficiaries - Sabbih, Mostafa Amir; Coudouel, Aline (World Bank, Washington, DC, 2021)
Most social protection agencies in Bangladesh do not invest enough in core processes of budgeting, management, enrolment, delivery and accountability. To maximize the impact of social protection (SP) programs, it is critical to: (1) align the allocation of resources with national policies and strategies; (2) design programs that are able to reach their intended beneficiaries with adequate coverage and level of benefits; (3) ensure efficiency in programming and financing; and (4) ensure efficiency in the actual delivery of programs at the local level. This policy note analyses point (4), the processes of delivery of SP programs, including beneficiary identification and provision of benefits. It highlights areas where challenges remain and proposes policy recommendations to address those.